Explicit cost dynamics : an alternative to activity-based costing - Yu-Lee, Reginald Tomas, 1964- (Wiley, 2001)
Traditional cost management systems typically defeat their own purpose by leading corporations to make decisions that ultimately do not optimize performance. These systems are the foundation for decisions that are made throughout the corporation.